Endocannabinoid System and Migraine Pain: An Update - Greco, Rosaria; Demartini, Chiara; Zanaboni, Anna M.; Piomelli, Daniele; Tassorelli, Cristina (Frontiers in Neuroscience, 2018)
The trigeminovascular system (TS) activation and the vasoactive release from trigeminal endings, in proximity of the meningeal vessels, are considered two of the main effector mechanisms of migraine attacks. Several other structures and mediators are involved, however, both upstream and alongside the TS. Among these, the endocannabinoid system (ES) has recently attracted considerable attention. Experimental and clinical data suggest indeed a link between dysregulation of this signalling complex and migraine headache. Clinical observations, in particular, show that the levels of anandamide (AEA) – one of the two primary endocannabinoid lipids – are reduced in cerebrospinal fluid and plasma of patients with chronic migraine, and that this reduction is associated with pain facilitation in the spinal cord. AEA is produced on demand during inflammatory conditions and exerts most of its effects by acting on cannabinoid (CB) receptors. AEA is rapidly degraded by fatty acid amide hydrolase (FAAH) enzyme and its levels can be modulated in the peripheral and central nervous system by FAAH inhibitors. Inhibition of AEA degradation via FAAH is a promising therapeutic target for migraine pain, since it is presumably associated to an increased availability of the endocannabinoid, specifically at the site where its formation is stimulated (e,g. trigeminal ganglion and/or meninges), thus prolonging its action.